‘Vorkuta is the capital of the world’ : people, place and the everyday production of the local - Pilkington, Hilary (The Sociological Review, 2012)
This article considers the relationship between people and place in the everyday production of the local. Based on empirical research with young people in Russia's far north it offers an empirically substantiated argument that processes of deterritorialization do not necessarily imply the disembedding of people from either the national or the local. Drawing on discursive psychological approaches to the construction of nationhood, the article demonstrates how national and local patriotisms are produced through a post-Soviet project of nationalism and an active programme of flagging the city by the city administration. Through an exploration of the everyday manifestation and articulation of ties between people and place, however, it also suggests some of the limitations to theories of the everyday discursive production of nationhood. Connections to place, it is argued, are not only unconscious or linguistic expressions of discursively produced subjects, but emotional and sensual responses to the material (urban space, nature, climate) and symbolic (hymns, flags, historical narratives) environment. This suggests the need to conceptualize place as a site of the active production and enactment of subjectivity, which is itself not only the product of language and discourse but of experience, affect and ‘matter’.